(Des)judicialização da saúde: um debate atual e necessário, com ênfase no âmbito municipal - Gonçalves, Cristian David (2020)
The Fundamental Social Right to Health finds relevant constitutional shelter, deserving due attention and realization, with a better implementation of public policies in this area. The high service deficit associated with other situations, especially at the municipal level, the gateway to the SUS, has strengthened the instrument of judicialization, judicial activism and the politicization of justice, with worrying protagonism of the Brazilian judiciary, causing developments and worrying reflexes, which deserve reflection. Thus, it is necessary to rethink and reflect on possible solutions, seeking (de) judicialization for a better implementation of public policies in the health area, in an egalitarian / isonomic, efficient and fair manner, with the use of a better dialogue. interinstitutional and the use of consensual mechanisms, like some practices, still embryonic but with positive results at the municipal level, which illustrate the present research.